1994
DOI: 10.1210/endo.134.5.8156934
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor distribution in rat testis: new implications for androgen regulation of spermatogenesis.

Abstract: The distribution of the androgen receptor (AR) in the adult rat testis was determined by biotin-streptavidin immunoperoxidase, employing tissue embedded in polyester wax which preserves antigenicity without compromising tissue preservation. The antibody probe used, which has been characterized previously, was an affinity purified, rabbit polyclonal antibody raised to the amino terminus peptide of the rat AR. Within the interstitial compartment, AR immunostaining was detected in some Leydig cells and all smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
66
0
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(89 citation statements)
references
References 4 publications
8
66
0
7
Order By: Relevance
“…Strong AR immunoreactivity was also observed in interstitial cells already on the first postnatal day and in Sertoli cells from 21 d onward, parallel to findings in other rodents (Kimura et al, 1993;Bremner et al, 1994;Zhou et al, 1996). The lack of AR immunoreaction for spermatogonial subtypes is also consistent with previous reports (Bremner et al, 1994;Vornberger et al, 1994;Matsumiya et al, 1999). AR functions as a ligand-dependent transcription factor, since ligand binding is a prerequisite for its transport to the nucleus where it accesses and regulates an array of androgen-responsive genes (Georget et al, 1997;Wang et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Strong AR immunoreactivity was also observed in interstitial cells already on the first postnatal day and in Sertoli cells from 21 d onward, parallel to findings in other rodents (Kimura et al, 1993;Bremner et al, 1994;Zhou et al, 1996). The lack of AR immunoreaction for spermatogonial subtypes is also consistent with previous reports (Bremner et al, 1994;Vornberger et al, 1994;Matsumiya et al, 1999). AR functions as a ligand-dependent transcription factor, since ligand binding is a prerequisite for its transport to the nucleus where it accesses and regulates an array of androgen-responsive genes (Georget et al, 1997;Wang et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…The action of androgen on GRTH protein expression in germ cells appears to be cell-specific, although germinal cells do not exhibit either gonadotropin or androgen binding activity (16,17). In contrast to the up-regulation of GRTH gene expression caused by hCG-induced androgen action in the Leydig cells, GRTH protein levels in purified pachytene spermatocytes were not affected by hormonal stimulation.…”
Section: Discussionmentioning
confidence: 84%
“…The interactions between PM cells and Sertoli cells provide an example of a mesenchymal-epithelial cell interaction (1). PM cells contain a high percentage of the androgen receptor (AR) (2,3) and provide a site for androgen signaling. It has been reported that the PM cells can synthesize several secretory products.…”
mentioning
confidence: 99%
“…The local actions of androgen on testis functions were initially demonstrated when testosterone alone, in the absence of the gonadotropins, leuteinizing hormone (LH), and follicle-stimulating hormone (FSH), could support spermatogenesis (11). Furthermore, AR has been detected in Sertoli, Leydig, PM, and spermatid cells (round and elongated) (2,3), and mice lacking functional AR develop testicular feminization syndrome (12). Previously, we have shown that Sertoli cellspecific AR Ϫ/y mice revealed incomplete germ cell development and lowered serum testosterone levels, which resulted in azoospermia and infertility (13).…”
mentioning
confidence: 99%